2018
DOI: 10.1159/000494513
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Mechanical Stress Stimulates GIT1-Dependent Mitogenic Signals in Rat Chondrocytes Through ERK1/2 Activity

Abstract: Background/Aims: The mitogenic effects of periodic mechanical stress on chondrocytes have been studied extensively, but the mechanisms whereby chondrocytes sense and respond to mechanical stimuli remain to be determined. We explored the question and verified the key role of G protein coupled receptor kinase interacting protein 1 (GIT1) signaling in periodic mechanical stress-induced chondrocyte proliferation. Methods: Two steps were undertaken in the experiment. In the first step, the cells were maintained und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Periodic mechanical load activates downstream protein kinase C (PKC) signals by stimulating chondrocytes α5β1 integrin, which can cause hyperpolarization of chondrocyte membrane (Wright et al, 1997). Mechanical signal pathways mediated by integrins are involved in the proliferation and matrix synthesis of chondrocytes, such as integrin β1-Src-GIT ArfGAP 1 (GIT1)-focal adhesion kinase (FAK) (Tyr576/577)extracellular regulated protein kinase 1/2 (ERK1/2), integrin β1-FAK(Tyr397)-ERK1/2, and integrin β1-Ca2+/calmodulin dependent protein kinase II (CaMKII)-Proline-rich tyrosine kinase 2 (Pyk2)-ERK1/2 signal pathway (Liang et al, 2017;Ren et al, 2018). Studies suggested that the death signaling pathway mediated by integrins also participated in the process that excessive mechanical load acting on cartilage explants (Jang et al, 2014).…”
Section: Integrins In Chondrocyte Mechanotransductionmentioning
confidence: 99%
“…Periodic mechanical load activates downstream protein kinase C (PKC) signals by stimulating chondrocytes α5β1 integrin, which can cause hyperpolarization of chondrocyte membrane (Wright et al, 1997). Mechanical signal pathways mediated by integrins are involved in the proliferation and matrix synthesis of chondrocytes, such as integrin β1-Src-GIT ArfGAP 1 (GIT1)-focal adhesion kinase (FAK) (Tyr576/577)extracellular regulated protein kinase 1/2 (ERK1/2), integrin β1-FAK(Tyr397)-ERK1/2, and integrin β1-Ca2+/calmodulin dependent protein kinase II (CaMKII)-Proline-rich tyrosine kinase 2 (Pyk2)-ERK1/2 signal pathway (Liang et al, 2017;Ren et al, 2018). Studies suggested that the death signaling pathway mediated by integrins also participated in the process that excessive mechanical load acting on cartilage explants (Jang et al, 2014).…”
Section: Integrins In Chondrocyte Mechanotransductionmentioning
confidence: 99%
“…The GIT1 protein is one of the key regulators of FA formation and cell migration (107,108). This protein has a complex structure, containing various domains and effector sites (109).…”
Section: Mirnas and Mechanotransduction Pathwaysmentioning
confidence: 99%
“…Several studies have reported the promoting effect of PMS on the proliferation of chondrocytes and matrix synthesis. [21][22][23][24] For example, van Valburg et al reported that joint traction provided mechanical stress to promote the repair of cartilage. 25 Additionally, Gao et al discovered that PMS significantly induced the expression of extracellular matrix (ECM) Col-2A1 and aggrecan in nucleus pulposus (NP) cells.…”
Section: Introductionmentioning
confidence: 99%